Estonia towards a single government approach. (OECD public governance reviews., 2011)
These OECD country reviews examine governance and public management issues from a comprehensive perspective, helping countries to identify how reforms can better reinforce each other in support of overall government objectives. They also examine reform strategies that have worked in other countries and provide advice as to which reforms can be appropriately adapted to a given country.